THE EFFECTIVENESS OF THE BLUD INFORMATION SYSTEM (SIBLUD) IN FINANCIAL MANAGEMENT AT THE BUDURAN HEALTH CENTER, SIDOARJO REGENCY - Khoirani, Sarah Safira; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the effectiveness of the Regional Public Service Agency Information System (SIBLUD) in financial management at the Buduran Health Center, Sidoarjo Regency. Effectiveness is measured based on the theory of Richard M. Steers through three main indicators, namely goal achievement, integration, and adaptation. Method: The research uses a descriptive qualitative approach with purposive sampling techniques to determine informants, including the treasurer of the Buduran Health Center as the admin and financial staff of the BOK. Data was obtained through interviews, observations, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawn. Results: The results of the study show that the implementation of SIBLUD is quite effective in accelerating the preparation of financial statements, SPJ, and budget management. In the indicator of achieving goals, the system has been proven to be able to increase efficiency even though it is still constrained by technical errors and manual inputs. In the integration indicators, SIBLUD has succeeded in uniting the financial process digitally centralized with routine socialization support. Meanwhile, in the adaptation indicators, some senior staff have difficulty switching from manual to digital systems, so the dependence on admins is still high. Novelty: This research contributes by examining the effectiveness of SIBLUD at the health center level using the theory of organizational effectiveness of Richard M. Steers (1985). These findings highlight the importance of system stability, continuous socialization, and increasing the digital literacy of senior health workers as the key to optimizing the implementation of SIBLUD.